Comparison of cushioned centrifugation and SpermFilter filtration on longevity and morphology of cooled-stored equine semen - Roach, J.; Schnobrich, M.; Ellerbrock, R.; Feijo, L.; Bradecamp, E.; Alvarenga, M. A. [UNESP]; Kline, K.; Canisso, I. (Bmj Publishing Group, 2016)
This study compares two methods for seminal plasma removal by evaluating sperm recovery rates, and motility and morphology of cooled-stored semen. Ejaculates were divided into three groups: control, filtration and cushioned centrifugation. Semen was extended to 25 million sperm/ml using a skim-milk-based extender and stored at 5 degrees C for all groups. Sperm motility (total motility (% TM) and progressive motility (% PM)) was determined at 0, 24, 48 and 72 hours by a computer-assisted sperm analyser. Sperm morphology was assessed using differential interference microscopy. Overall, % TM of the centrifugation group was significantly higher than the filter group, but not significantly different than the control. No significant difference in % TM or % PM was detected for the control group and filter. Cushioned centrifugation was a superior method to obtain progressively motile sperm compared with control (P = 0.03) and filter groups (P < 0.001). No significant difference was found for the per cent of normal sperm cells and detached heads between the groups. This study demonstrated that cushioned centrifugation was a superior method to remove seminal plasma while preserving % TM and enhancing % PM for stallions under cooled storage over three days. However, as the differences appear to be negligible, the SpermFilter may represent an alternative for farms lacking a centrifuge.